Ursolic Acid Limits Salt-Induced Oxidative Damage by Interfering With Nitric Oxide Production and Oxidative Defense Machinery in Rice - Long, Meijuan; Shou, Jianyao; Wang, Jian; Hu, Weizhen; Hannan, Fakhir; Mwamba, Theodore M.; Farooq, Muhammad A.; Zhou, Weijun; Islam, Faisal (Frontiers in Plant Science, 2020)
Crops frequently encounter abiotic stresses, and salinity is a prime factor that suppresses plant growth and crop productivity, globally. Ursolic acid (UA) is a potential signaling molecule that alters physiology and biochemical processes and activates the defense mechanism in numerous animal models; however, effects of UA in plants under stress conditions and the underlying mechanism of stress alleviation have not been explored yet. This study examined the effects of foliar application of UA (100 μM) to mitigate salt stress in three rice cultivars (HZ, 712, and HAY). A pot experiment was conducted in a climate-controlled greenhouse with different salt stress treatments. The results indicated that exposure to NaCl-induced salinity reduces growth of rice cultivars by damaging chlorophyll pigment and chloroplast, particularly at a higher stress level. Application of UA alleviated adverse effects of salinity by suppressing oxidative stress (H2O2, O2–) and stimulating activities of enzymatic and non-enzymatic antioxidants (APX, CAT, POD, GR, GSH, AsA, proline, glycinebutane), as well as protecting cell membrane integrity (MDA, LOX, EL). Furthermore, UA application brought about a significant increase in the concentration of leaf nitric oxide (NO) by modulating the expression of NR and NOS enzymes. It seems that UA application also influenced Na+ efflux and maintained a lower cytosolic Na+/K+ ratio via concomitant upregulation of OsSOS1 and OsHKT1;5 in rice cultivars. The results of pharmacological tests have shown that supply of the NO scavenger (PTI) completely reversed the UA-induced salt tolerance in rice cultivars by quenching endogenous NO and triggering oxidative stress, Na+ uptake, and lipid peroxidation. The PTI application with UA and sodium nitroprusside (SNP) also caused growth retardation and a significant increase in Na+ uptake and oxidative stress in rice cultivars. This suggests that UA promoted salt tolerance of rice cultivars by triggering NO production and limiting toxic ion and reactive oxygen species (ROS) accumulation. These results revealed that both UA and NO are together required to develop a salt tolerance response in rice.